MANGROVE OF BERAU: ECOLOGICAL CONDITION, FISHERIES, AND MANAGEMENT OPTIONS - Ivana Yuniarti; Triyanto Triyanto; Nirmalasari Idha Wijaya; Fajar Sumi Lestari; Fajar Setiawan; Sutrisno Sutrisno (Research Center for Fisheries, 2016)
Mangrove area of Berau District, East Kalimantan Province is an important buffering zone for Derawan Islands. It also becomes a distinctive habitat for commercial fisheries commodity. Land conversion into shrimp ponds has threatened its sustainability. This paper summarizing its ecological condition, fisheries, and management options presents a guideline for the decision makers about what strategies can be applied in conserving the mangrove sustainability. Overall, the ecological condition is proven to support sustainable fisheries practice; such as shrimp and crab silvofisheries. Moreover, the calculation of firewood economic value shows that a sustainable commercial firewood production is another option that can be established to support local economic activities. In addition, a well managing ecotourism may be considered by local government considering its potential for local economic growth.